Development and Application of Carbon‐Layer‐Stabilized, Nitrogen‐Doped, Bamboo‐Like Carbon Nanotube Catalysts in CO2 Hydrogenation. Issue 10 (5th October 2018) - Sikora, Emőke; Prekob, Ádám; Halasi, Gyula; Vanyorek, László; Pekker, Péter; Kristály, Ferenc; Varga, Tamás; Kiss, János; Kónya, Zoltán; Viskolcz, Béla
Abstract: Nitrogen‐doped, bamboo‐like carbon nanotubes (BCNTs) were synthesized from butylamine by catalytic chemical vapor deposition (CCVD method). The nanotubes were oxidized by H2 SO4 /HNO3 treatment and used to prepare calcium alginate gelled BCNT spheres. These beads were first carbonized and then Pd, Rh and Ni nanoparticles were anchored on the surface of the spheres. These systems were then applied as catalysts in CO2 hydrogenation. The BCNT support was examined by Raman spectroscopy, dynamic light scattering (DLS) and X‐ray photoelectron spectroscopy (XPS). The prepared catalysts were characterized by HRTEM and SEM. The oxidation pretreatment of BCNTs was successful, with the electrokinetic potential of the water‐based dispersion of BCNTs measuring −59.9 mV, meaning the nanotube dispersion is stable. Pyridinic and graphitic types of incorporated nitrogen centers were identified in the structure of the nanotubes, according to the XPS measurements. The Pd‐containing BCNT sphere catalyst was the most efficient in the catalytic studies. The highest conversion was reached on the Pd catalyst at 723 K, as well as at 873 K. The difference in the formation rate of CO was much less at 873 K between the Pd and Rh compared to the 723 K values. Accordingly, the application of Pd‐containing BCNT/carbon‐supported catalyst favored the generation of CO. However, the Ni‐BCNT/carbon catalyst leads to the formation of CH4 as the major product. Abstract : Simply the best : Nitrogen‐doped, bamboo‐like carbon nanotubes (BCNTs) were synthesized from butylamine by catalytic chemical vapor deposition. The nanotubes were used to prepare calcium alginate gelled BCNT spheres which were subsequently carbonized and loaded with Pd, Rh and Ni nanoparticles. These systems were used as catalysts in CO2 hydrogenation, with the Pd derivative found to demonstrate the highest conversion at 723 and 873 K.